Asylum : a memoir & manifesto [book club bag] - Okporo, Edafe (Simon & Schuster Paperbacks, 2023)
Offers an urgent call to action for immigration justice by a Nigerian asylee and global gay rights and immigration activist Edafe Okporo. On the eve of Edafe Okporo's twenty-sixth birthday, he was awoken to a violent mob outside his window in Abuja, Nigeria. The mob threatened his life after discovering the secret Edafe had been hiding for years -- that he is a gay man. He fled for his life to New York City and would go on to spend the next six months at an immigration detention center in Elizabeth, New Jersey. After navigating the confusing, often draconian, US immigration and legal system, Edafe was finally granted asylum. This volume is Edafe's eye-opening, thought-provoking memoir and manifesto, which documents his experiences growing up gay in Nigeria, fleeing to America, navigating the immigration system, and making a life for himself as a Black, gay immigrant. Alongside his personal story is a call to action--not only for immigration reform but for a just immigration system for refugees everywhere. This book imagines a future where immigrants and asylees are treated with fairness, transparency, and compassion. It aims to help us understand that home is not just where you feel safe and welcome but also how you can make it feel safe and welcome for others. --From publisher description.